Shortcomings analysis of iterative methods to solve ill-condition systems of linear equations / Nur Nabil Nadiah Elias - Elias, Nur Nabil Nadiah (2020)
An iterative method is a mathematical procedure in computational mathematics. It had been used to generate a sequence of improving approximation solutions for problems by using an initial guess where nth approximation is derived from the previous one. In this research, three iterative method which are the Jacobi method, the Gauss-Seidel method and the Successive Over-Relaxation had been used. The Jacobi method, the Gauss-Seidel method and the Successive Over-Relaxation will be used to solve the ill- conditioned linear systems. This study is conducted to assess the performance of these iterative methods by means of numerical studies. This is to provide satisfactory explanation on the convergence problems and also an insight on how these iterative methods work.